Investigating the Correlation Between Income Inequality and Economic Growth - Sidhu, Brahmaleen Kaur (Journal of Global Economy, Business and Finance, 2024)
The relationship between income inequality and economic growth has been the subject of extensive theoretical debate, with varying predictions on whether inequality fosters or hinders growth. This study investigates the relationship between income inequality and economic growth using a fixed-effects model, estimated on cross-country data spanning from 1963 to 2015. The findings suggest a robust negative correlation between income inequality and economic growth, with stronger effects observed in more developed countries.